Data science at the command line - Janssens, Jeroen (O'Reilly Media, 2014)
"We data scientists love to create exciting data visualizations and insightful statistical models. However, before we get to that point, usually much effort goes into obtaining, scrubbing, and exploring the required data. The command line, although invented decades ago, is an amazing environment for performing such data science tasks. By combining small, yet powerful, command-line tools you can quickly explore your data and hack together prototypes. New tools such as GNU Parallel, jq, and Drake allow you to use the command line for today's data challenges. Even if you're already comfortable processing data with, for example, R or Python, being able to also leverage the power of the command line can make you a more efficient data scientist. We will make use of the Data Science Toolbox, which is a free, open-source virtual environment that allows everybody to get started with data science in minutes. The Data Science Toolbox runs not only on Linux, but also on Mac OX X and Microsoft Windows, so everybody can participate with this hands-on webcast."--Resource description page.
Title from resource description page (viewed Oct. 15, 2014)
Keywords: User interfaces (Computer systems); User-Computer Interface; Interfaces utilisateurs (Informatique); Electronic videos